Bone mineral density and fractures in congenital adrenal hyperplasia: Findings from the dsd‐LIFE study. (20th January 2020) - Riehl, Gabriel; Reisch, Nicole; Roehle, Robert; Claahsen van der Grinten, Hedi; Falhammar, Henrik; Quinkler, Marcus
Abstract: Background: In patients with congenital adrenal hyperplasia (CAH) type and doses of glucocorticoids used as well as sex hormone secretion during puberty have important actions on bone mineral density (BMD) in adulthood. Aim: To evaluate BMD in adult CAH patients depending on current glucocorticoid therapy and on androgen levels in adulthood and at age 16 years. Methods: We included 244 CAH patients from the dsd‐LIFE cohort (women n = 147, men n = 97; salt‐wasting n = 148, simple‐virilizing n = 71, nonclassical n = 25) in which BMD and bloods were available. Clinical and hormonal data at age 16years were retrieved from patients' files. Results: Simple‐virilizing women showed lower BMD compared to salt‐wasting women at trochanter (0.65 ± 0.12 vs 0.75 ± 0.15 g/cm 2 ; P  < .050), whole femur T‐score (−0.87 ± 1.08 vs −0.16 ± 1.24; P  < .05) and lumbar T‐score (−0.81 ± 1.34 vs 0.09 ± 1.3; P  < .050). Fracture prevalence did not differ significantly between the CAH groups. Prednisolone vs. hydrocortisone only therapy caused worse trochanter Z‐score (−1.38 ± 1.46 vs −0.47 ± 1.16; P  < .050). In women lumbar spine, BMD correlated negatively with hydrocortisone‐equivalent dose per body surface (r 2  = 0.695, P  < .001). Furthermore, BMI at age 16years correlated positively with lumbar spine T‐score (r 2  = 0.439, P  = .003) and BMD (r 2  = 0.420, P  = .002) in women. The androstenedione/testosterone ratio at age 16years correlated positively with lumbar spine Z‐score in women (r 2  = 0.284, P  = .024) and trochanter Z‐score in men (r 2  = 0.600, P  = .025). Conclusion: Higher glucocorticoid doses seemed to cause lower BMD especially in women. Prednisolone appeared to have more detrimental effects on BMD than hydrocortisone. Higher glucocorticoid doses (lower androstenedione/testosterone ratio) during adolescence may cause lower BMD in adulthood.